An Economic Analysis of Maritime Piracy and its Control. (4th August 2013) - Hallwood, Paul; Miceli, Thomas J.
Abstract: Modern‐day piracy on the high seas poses a serious threat to international shipping. This paper develops an economic of model of piracy that emphasizes the strategic interaction between the efforts of pirates to locate potential targets, and shippers to avoid contact. Implementation of optimal enforcement policies is complicated by the need for international cooperation in the apprehension and prosecution of pirates. Free riding and other problems therefore impede the effectiveness of current international laws against piracy.